The prognostic value of bone marrow involvement at the molecular level in aggressive lymphoma. Issue 1 (2nd January 2017) - Goldschmidt, Neta; Darawshy, Fares; Kleinstern, Geffen; Slyusarevsky, Elena; Pogrebijski, Galina; Krichevsky, Svetlana; Ben-Yehuda, Dina; Gatt, Moshe E.
Abstract: We retrospectively studied the prognostic role of molecular (gene rearrangement, GRR) bone marrow (BM) involvement in diffuse large B-cell lymphoma (DLBCL, 424 patients) and in peripheral T-cell lymphoma (PTCL, 67 patients). When correlating BM GRR to histological findings at diagnosis, the GRR test was more sensitive ( p = 0.036) but less specific ( p < 0.0001) in PTCL than in DLBCL. For DLBCL (but not PTCL), a positive BM GRR correlated with advanced stage ( p = 0.0001) and high IPI ( p = 0.002), and worsened the progression free survival (PFS) ( p = 0.05) and overall survival (OS) ( p = 0.01), irrespective of rituximab treatment. Histologic negative/GRR positive cases had worse PFS/OS ( p < 0.0001) than histologic/GRR double negative cases, however BM GRR was not an independent prognostic survival factor. End-of-treatment BM GRR did not predict survival. We conclude that BM GRR is unjustified as a prognostic tool for PTCL and should be reserved for a subset of DLBCL patients with negative histology of the BM.